2016
DOI: 10.3164/jcbn.16-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistent reflux symptoms cause anxiety, depression, and mental health and sleep disorders in gastroesophageal reflux disease patients

Abstract: Some patients with gastroesophageal reflux disease experience persistent reflux symptoms despite proton pump inhibitor therapy. These symptoms reduce their health-related quality of life. Our aims were to evaluate the relationship between proton pump inhibitor efficacy and health-related quality of life and to evaluate predictive factors affecting treatment response in Japanese patients. Using the gastroesophageal reflux disease questionnaire, 145 gastroesophageal reflux disease patients undergoing proton pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Previous studies showed bidirectional association between GERD and psychological problems such as anxiety, depression, sleep disturbance, and insomnia. 35 , 57 - 59 , In our results, positive history of anxiety (OR 1.24, 95% CI 1.11 - 1.40) and insomnia (OR 1.36, 95% CI 1.21 - 1.54) were significantly associated with GERD and frequent GERD.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies showed bidirectional association between GERD and psychological problems such as anxiety, depression, sleep disturbance, and insomnia. 35 , 57 - 59 , In our results, positive history of anxiety (OR 1.24, 95% CI 1.11 - 1.40) and insomnia (OR 1.36, 95% CI 1.21 - 1.54) were significantly associated with GERD and frequent GERD.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have shown that patients, particularly those with a poor response to PPIs, were more likely to show higher levels of anxiety and depression, and these partial PPI responders were most common in the NERD group among the subtypes of GERD. 38 Therefore, the relationship between anxiety, depression, and GERD involves a complex interplay of various mechanisms, and a multidisciplinary approach is needed to understand this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…8,[31][32][33] It has been demonstrated that the higher the level of anxiety and depression, the poorer, the effectiveness of acid-suppressing therapy, and thus psychological factors can be used as a predictor of anti-reflux treatment. [34][35][36] Therefore, patients with GERD with anxiety and depression were included in the present study. GERD-AD group was recruited according to the GerdQ, endoscopy, and Hamilton Anxiety and Depression Rating Scale, and the GERD-AD group did not overlap with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, GERD can also increase the incidence of psychological disorders such as anxiety and depression. 7,8 Current diagnostic methods for GERD include symptom questionnaires and 24-hour pH monitoring, 9 high-resolution esophageal manometry, 10 endoscopy, radionuclide gastroesophageal reflux test, and proton pump inhibitor (PPI) diagnostic treatments. 11 Among them, 24-hour pH monitoring is the most commonly used method with a high specificity.…”
Section: Introductionmentioning
confidence: 99%